2016
DOI: 10.1080/10246029.2016.1155466
|View full text |Cite
|
Sign up to set email alerts
|

The fate of hostages: Nigeria's conflict theatres in comparative perspective

Abstract: The violence against hostages in Nigeria's armed conflicts is alarming. Killings, physical mutilation, sexual abuse, forced marriage, religious persecution, forced labour and conscription of hostages have all been recorded during Nigeria's conflicts in recent times. This trend has increased the concern for the fate of hostages in the country. However, there have been a few exceptions: some have escaped from their abductors, while a few others have been released for ransom or rescued by security operatives. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Government also made efforts to fight Boko Haram insurgency; wage war against terrorism, kidnapping and hostage taking; and above all political instability by fortifying all the security architecture of the land. However, security experts have argue that the application of suppressive force interlaced with some counter-insurgency strategies, hence, the approach to fighting insecurity generates retaliatory violence (Akinjuru & Ruddock, 2016;Ichili, 2016;Oyewole, 2016;Sampson, 2016).…”
Section: The Interventions Of Political Leadership Towards Image Builmentioning
confidence: 99%
See 1 more Smart Citation
“…Government also made efforts to fight Boko Haram insurgency; wage war against terrorism, kidnapping and hostage taking; and above all political instability by fortifying all the security architecture of the land. However, security experts have argue that the application of suppressive force interlaced with some counter-insurgency strategies, hence, the approach to fighting insecurity generates retaliatory violence (Akinjuru & Ruddock, 2016;Ichili, 2016;Oyewole, 2016;Sampson, 2016).…”
Section: The Interventions Of Political Leadership Towards Image Builmentioning
confidence: 99%
“…NHRC was established to create an environment for the extrajudicial recognition, to fight any form of human right violations, and the promotion, protection and enforcement of human rights. However, the violent killings, physical mutilation, sexual abuse, forced marriage and labour, religious persecutions, conscription of hostages among other nefarious treatment have all been recorded in Nigeria's Fourth Republic (Oyewole, 2016). All these instances negate the international treaty of human rights protection that Nigeria state did signed.…”
Section: The Interventions Of Political Leadership Towards Image Builmentioning
confidence: 99%
“…In Africa for instance, statistics showed that the following countries: Ghana, Mali, Kenya, Cameroon, Somalia, Nigeria, are prone to kidnapping related activities and threats (Okeowo, 2013;Onuoha & Okolie-Osemene, 2019). In fact, Nigeria is regarded as the arrow head of operations on kidnapping activities having received half of the kidnapping statistics in the entire Africa (Ngwama, 2014;Oyewole, 2016a;Assanvo & Okereke, 2019;Attah et al, 2021). Although, kidnapping and hostage taking is not a new development in Nigeria, its rates, dimensions, and implications are what have continually generated attention in the 21 st century (Ebohon & Ifeadi, 2012;Ngwama, 2014;Okorie-Ajah, Nwokeoma & Okpan, 2018;Tade, Ojedokun & Aderinto, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The significant kidnapping cases in Niger Delta started as a political agitation for the development need of the region based on the exploration of oil therein. This region began the formal act of kidnapping in the entire country when foreigners working at multinational oil companies -Shell Petroleum Development Company of Nigeria Limited -Total -Chevron Nigeria Limited -Mobil Producing Nigeria Limitedwere kidnapped (Akpan, 2010;Badiora, 2015;and Oyewole, 2016a). These kidnapping activities usually come with requests for financial returns before the release of such victims.…”
Section: Introductionmentioning
confidence: 99%
“…Many children and young men and women were conscripted to join the insurgent campaign and served the self-proclaimed caliphate as fighters, spies, traps, armor bearers, transporters/porters, cameramen, technicians, cooks, sex slaves and medics. 31 In 2014, Boko Haram was reported to have outsourced parts of its campaign in Nigeria to some Nig eriens for US$3,085 (N500, 000: Nigerian Naira). 32 Besides locally produced weapons, the insurgent relied on trans-Sahel arms trafficking.…”
mentioning
confidence: 98%